If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(a + 5) + -2(a + -5) = 0 Reorder the terms: 4(5 + a) + -2(a + -5) = 0 (5 * 4 + a * 4) + -2(a + -5) = 0 (20 + 4a) + -2(a + -5) = 0 Reorder the terms: 20 + 4a + -2(-5 + a) = 0 20 + 4a + (-5 * -2 + a * -2) = 0 20 + 4a + (10 + -2a) = 0 Reorder the terms: 20 + 10 + 4a + -2a = 0 Combine like terms: 20 + 10 = 30 30 + 4a + -2a = 0 Combine like terms: 4a + -2a = 2a 30 + 2a = 0 Solving 30 + 2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 2a = 0 + -30 Combine like terms: 30 + -30 = 0 0 + 2a = 0 + -30 2a = 0 + -30 Combine like terms: 0 + -30 = -30 2a = -30 Divide each side by '2'. a = -15 Simplifying a = -15
| 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 | | 5x^2-lnx=0 | | -10-7m=-6m | | 3k+4=5k-10 | | 10+7p=24 | | 18x-8=13x-33 | | 2x-6+21=-3 | | -b-10=10+10+9b | | 4x-84=72-9x | | 4(2x+9)=-46+10 | | 2(x-3)-5(x-1)=4 | | -2x-5y=12forY | | b-10=10+10+9b | | 3(5x+6)-2(3-4x)=-11 | | 5z+14=7z-30 | | 4n^2-12n-320=0 | | x*x-100=0 | | 10-d=d-8 | | 340=x*490 | | 5(3t-4)-6=12t+4 | | -3r+6=r-6 | | 10-3y=6 | | 8u=7u+1 |